Deliverable 5.10 Geostatistical Library V2 - Renard, Didier; Ors, Fabien; Caumont, Hervé (Zenodo, 2022)
The INTAROS project develops an integrated Arctic Observation System (iAOS) by extending, improving and unifying existing systems in the different regions of the Arctic. Within INTAROS, WP5 (Data integration and management) is tasked with designing and implementing evolutions of the cloud platform with geo statistical tools for services as part of the iAOS. The work effort in Task 5.4 has been to design, develop and distribute a Geostatistical Library to be used as a scientific toolbox in some different data analysis workflows (e.g. for the iAOS showcase applications). The first version of the Geostatistical Library (v1) was considering CTD data provided by IMR for estimating ocean temperature maps in the Barents Sea (D5.6). This document describes the new version of the Geostatistical Library (v2) where some additional capabilities have been developed. A set of new functions deals with weather stations and AROME Arctic model in order to estimate snow depth maps in Isfjorden (Svalbard). Another set supports the combination of ICES CTD dataset, GINR trawls dataset and GEBCO bathymetry for estimating bottom ocean temperature maps along the West Greenland coast. Reviewed by: Hanne Sagen and Torill Hamre